Therapeutic Strategies for Alzheimer's and Parkinson's Diseases by Means of Drug Delivery Systems - Cunha, S.; H. Amaral, M.; M. Sousa Lobo, J.; C. Silva, A. (Current Medicinal Chemistry, 2016)
Alzheimer’s and Parkinson’s diseases are prevalent neurodegenerative disorders worldwide, which are essentially related to aging. Within the remarkable era of nanomedicine, nowadays several delivery systems have been suggested to improve the treatment of these disorders, namely, liposomes, micelles, nanoparticles (polymeric, lipid, metallic and inorganic), exosomes, dendrimers and fullerenes. The advantage that has been claimed to these delivery systems is that they facilitate the passage of drugs through the blood brain barrier (BBB), enabling targeting before body degradation, and increasing therapeutic efficacy, comparied to conventional pharmaceutical dosage forms. This review article provides a state of the art regarding the drug delivery systems that have been studied for the treatment of Alzheimer’s and Parkinson’s diseases. It begins with a brief description of the central nervous system (CNS) and the mechanisms involved in the development of these diseases. Later, some examples of drugs used in the treatment of these neurodegenerative diseases are presented, which are currently available in conventional pharmaceutical dosage forms, and in new drug delivery systems that are under development.
Keywords: Exosomes